Reação postural de pacientes com doença de Parkinson e idosos sadios no teste de retropulsão instrumentado - Morais, Luana Carolina de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Title: Postural response in patients with Parkinson's disease and healthy elderly on instrumented retropulsion test Introduction: Parkinson's disease (PD) is characterized by a dopamine deficit necessary to movement control. Thus, signs and symptoms motors arise, for example, postural instability, which has a small response for drugs therapy. Since PD patients show deficits in anticipatory and compensatory postural adjustment, the present study manipulated the expectation of an external disturbance with an instrument that replicated the retropulsion test (item 30 of the Unified Parkinson's Disease Rating Scale (UPDRS) called unexpected retropulsion test (URT) and the same test as expected (ERT) to expand knowledge of the compensatory postural reactions and postural instability. Objective: To investigate the compensatory postural reactions and balance recovery in healthy elderly and patients with PD through URT and ERT. Method: 34 subjects were evaluated (17 healthy elderly and 17 elderly with PD (stage 1 to 2.5 of the Hoehn & Yahr). For exclusion's criteria of the study, participants answered the anamnesis. For the screening of cognitive functions was used the Mini Mental State Examination (MMSE) and to assess the degree of involvement of the disease it was applied the UPDRS. For applications of URT and ERT, a device was designed and constructed to ensure the implementation of a customized force (5% of the participant body weight), ensuring the displacement of the center of mass (CM). When an expectation of external disturbance was manipulated, the first attempt was made unexpectedly to all participants and the other attempts (4) in the expected way. Spatiotemporal variables were calculated: the time from the beginning of the movement and removal of the heel from the ground, width, length and velocity of the recovery step; relative angles of the hip, knee and ankle at the beginning of the movement, and the time of removal of the...

Introdução: A doença de Parkinson (DP) é caracterizada pelo déficit de dopamina, necessária para controlar os movimentos. Sinais e sintomas motores surgem, como a instabilidade postural, que apresenta pequena resposta à terapia medicamentosa. Como pacientes com DP mostram déficits nos ajustes posturais antecipatórios e compensatórios, o presente estudo manipulou a expectativa de uma perturbação externa, com um instrumento que reproduziu o teste de retropulsão (item 30 da Unified Parkinson's Disease Rating Scale (UPDRS)) chamado teste de retropulsão inesperado (TRI) e o mesmo teste de forma esperada (TRE), para aprofundar o conhecimento sobre a reação postural compensatória e a instabilidade postural. Objetivo: Investigar a reação postural compensatória e a recuperação de equilíbrio de idosos sadios e de pacientes com DP por meio do TRI e TRE. Método: Foram avaliados 34 idosos, sendo 17 idosos sadios e 17 idosos com DP (estágio de 1 a 2,5 da escala de Hoehn & Yahr - HY). Para o rastreio das funções cognitivas foi utilizado o Mini Exame do Estado Mental (MEEM) e para ter conhecimento do grau de acometimento e estadiamento da doença aplicou-se a UPDRS e a HY. Para as aplicações dos TRI e TRE, um equipamento foi desenhado e construído de forma a garantir a aplicação de uma força personalizada (5% do peso corporal), assegurando o deslocamento do centro de massa (CM). Quando a expectativa da perturbação externa foi manipulada, a primeira tentativa foi realizada de forma inesperada para todos os participantes e, as demais tentativas (4), de forma esperada. Foram calculadas variáveis espaço-temporais: tempo entre o início do movimento e a retirada do calcâneo do solo, comprimento, largura e velocidade do passo de recuperação; ângulos relativos do quadril, joelho e tornozelo no início do movimento, no momento da retirada do calcâneo e o toque no solo; cinéticas: deslocamento do centro de pressão (CoP)...
Keywords: Physical education and training; Educação fisica; Educação fisica para idosos; Parkinson, Doença de; Postura humana; Capacidade motora